Expression, purification and crystallization of Asrij, A novel scaffold transmembrane protein - Motiwala, Zenia; Darne, Priti; Prabhune, Asmita; Inamdar, Maneesha S.; Kulkarni, Kiran (Journal of Membrane Biology, 2021)
Asrij/OCIAD1 is a scaffold transmembrane protein belonging to the Ovarian Carcinoma Immunoreactive Antigen Domain containing protein family. In Drosophila and mouse models, Asrij localizes at the endosomal and mitochondrial membrane and is shown to regulate the stemness of hematopoietic stem cells. Interaction of Asrij with ADP Ribosylation Factor 1 (Arf1) is shown to be crucial for hematopoietic niche function and prohemocyte maintenance. Here, we report the heterologous expression, standardization of detergents and purification methodologies for crystallization of Asrij/OCIAD1. To probe the activity of bacterially expressed Asrij, we developed a protein complementation assay and conclusively show that Asrij and Arf1 physically interact. Further, we find that sophorolipids improve the solubility and monodispersibility of Asrij. Hence, we propose that sophorolipids could be novel additives for stabilization of membrane proteins. To our knowledge, this is the first study detailing methodology for the production and crystallization of a heterologously expressed scaffold membrane protein and will be widely applicable to understand membrane protein structure and function. Graphic
Keywords: Asrij/OCIAD1; Membrane protein crystallography; sophorolipids